Africa and China Higher Education Cooperation: Establishing Knowledge Sharing Partnership between Students - (:unkn) unknown (My University, 2017)
Knowledge sharing should not be confused neither with data sharing nor with information sharing; the knowledge sharing includes data and information sharing, skills and expertise communication, ideas exchange. Since the fourth FOCAC held in Egypt in 2009, many policies have been added to reinforce Africa and China educational cooperation, especially in the area of higher education. And this paper intends to look more closely at this area, particularly with regards to the possibility of establishing and strengthening knowledge sharing, ideas exchange between Africa and China, through African and Chinese students' partnership. Based on the documented trends on Africa and China higher education cooperation, partnership and exchanges, questionnaire surveys, interviews and observations, the author tries to find out whether African students who are studying in China will to collaborate or not with Chinese students during their studies and researches. What are their motivations to cooperate with their Chinese classmates, and how should we beef up and promote knowledge sharing between African and Chinese people through University students' knowledge sharing partnership?
Keywords: African Research